La Revisión por la dirección: del análisis de los elementos a la síntesis del sistema – metodología (2022)
The Review by the Management is the tool that enables the organization's top management to consolidate the results of the management system and to be accountable for the system's performance. This methodology proposes review the management system from a synthesis perspective. This means moving from analyzing the inputs and making separate decisions for each, to establishing the links between them and integrate other elements of the organization into the review process and determine how they relate to the management system. This in order to achieve a broader vision of the organization, understanding it as a system and facilitating decision making.